AN EMPIRICAL STUDY ON PERCEPTION AND PURCHASE BEHAVIOUR OF WOMEN CONSUMER TOWARDS WASHING MACHINE (WITH SPECIAL REFERENCE TO CHENGALPATTU, CHENNAI AND KANCHIPURAM DISTRICTS) - Mrs.M. Meerabai , Dr.K.Selvasundaram (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Women are considered to be the most attractive and influential segment of present consumer market as they control almost 80 percent of household spending. Researchers have conducted various studies on unique buying behaviour of women consumers over the past few decades. The main reason for various studies is that the increase in purchasing power of women all over the world as they largely entered into workforce and they have tremendous financial capacity. They influence the majority decision relating family purchases. Especially working women spend their considerable time and income in selecting best for their family.The object of present study is to examine the consumer behaviour with special focus on women consumers and their need for select products and services. In this paper, we shall focus on their general buying behaviour and try to find out if there is an association between certain factors with few variables of women’s buying behaviour. The study covered the area of Chengalpattu, Chennai and Kancheepuram District.